2020
DOI: 10.1101/2020.03.06.978973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repeatable differences in exploratory behaviour predict tick infestation probability in wild great tits

Abstract: Ticks are parasites that feed on the blood of various vertebrate hosts, including many species of bird. Birds can disperse ticks over short and long distances, therefore impacting tick population dynamics. The likelihood that birds attract ticks should depend on their behaviour and the environment. We studied various key ecological variables (breeding density, human disturbance) and phenotypic traits (exploratory behaviour; body condition) proposed to predict tick burden in great tits (Parus major). Our study … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(113 reference statements)
1
1
0
Order By: Relevance
“…This may explain why we also found strong evidence for population-specific (i.e., macroscale) temporal variation in selection (population × year effects). Other factors may also play a key role here, for example, predator-or parasite-induced selection varying more among years in populations with high versus low overall levels of these biological factors (32)(33)(34)(35). Our finding of plot-specific (i.e., microscale) Previous studies revealed a key role of social environmental variation by demonstrating that selection on exploration behavior (18,28) and aggression (22) varies with breeding density within populations.…”
Section: Discussionsupporting
confidence: 51%
“…This may explain why we also found strong evidence for population-specific (i.e., macroscale) temporal variation in selection (population × year effects). Other factors may also play a key role here, for example, predator-or parasite-induced selection varying more among years in populations with high versus low overall levels of these biological factors (32)(33)(34)(35). Our finding of plot-specific (i.e., microscale) Previous studies revealed a key role of social environmental variation by demonstrating that selection on exploration behavior (18,28) and aggression (22) varies with breeding density within populations.…”
Section: Discussionsupporting
confidence: 51%
“…testosterone level) [13] and behavioural (e.g. foraging style) [14] traits, and host-extrinsic factors that are associated with environmental (e.g. vegetation cover and type) and climatic (e.g.…”
Section: Introductionmentioning
confidence: 99%